PENGEMBANGAN BAHAN AJAR KIMIA DASAR I TERINTEGRASI MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR MAHASISWA TINGKAT : UNIVERSITAS SWASTA DI SUMATERA UTARA - Mastiur Verawaty Silalahi; Eka Kartika Silalahi; Irene Vania Tobing (LP2MTBM MAKARIOZ, 2018)
This research is Development Research (R & D). The purpose of this study (1) is to find out the feasibility test and perceptions of lecturers on the development of basic chemistry teaching materials I integrated Problem Based Learning (PBL) models, (2) to compare student learning outcomes using basic I chemistry teaching materials integrated Problem Based models Learning (PBL) and basic I chemistry teaching materials used by universities.The stages carried out in this study include (1) analyzing basic chemistry teaching materials used in universities (2) developing basic I chemistry teaching materials that are integrated with Problem Based Learning models (3) standardizing or feasibility testing of basic chemical teaching materials on expert validators and some chemistry lecturers (4) carried out the implementation of basic chemistry teaching materials I at UMTS (5) conducted an analysis of the effect of basic chemistry teaching materials I which integrated the Problem Based Learning model to improve student learning outcomes.Based on the aspect of content feasibility in basic chemistry teaching materials I, which is integrated with the Problem Based Learning model and the basic chemistry teaching materials used in higher education institutions have an average of 3.96 and 2.89. The aspects of language feasibility in basic chemistry teaching materials I that are integrated with problem based learning models and basic chemistry teaching materials used in tertiary institutions are 3.88 and 3.02. The feasibility aspect of presentation in the basic chemistry teaching material I which integrated the problem based learning model and basic chemistry teaching materials used in higher education had an average of 3.85 and 3.00. The feasibility aspect of the basic chemistry teaching material I, which is integrated with the problem based learning model and the basic chemistry teaching materials used in universities, has an average of 3.88 and 3.20. The effectiveness of using basic chemistry teaching materials I integrated the problem based learning model for improving student achievement, according to the results of testing the Independent Sample T-Test data of 0,000 <0,05, which concluded that Ho refused and Ha accepted. The percentage of effectiveness in the control and experimental classes was 73.45% and 81.81%.